Representative sample survey on factors determining the Czech physicians' awareness of generic drugs and substitution - J. Maly; E. Zimcikova; J. Babica; A. A. Kubena; J. Kostriba; K. Mala-Ladova (BMC, 2019)
Abstract Background Generic drugs and generic substitution belong to the tools by which healthcare costs may be reduced. However, low awareness and reluctance among healthcare professionals towards generic drugs may negatively affect the rational use of generic substitution. Methods The study aimed to analyze opinions and attitudes towards generic drugs and generic substitution among Czech physicians including their understanding of generic substitution legislative rules and the physicians´ previous experience in this field. Using random allocation, 1551 physicians practicing in the Czech Republic were asked to participate in the sociological representative survey conducted from November to December 2016, through face-to-face structured interviews comprising 19 items. Factor analysis as well as reliability analysis of items focused on legal rules in the context of physicians' awareness were applied with p-value of < 0.05 as statistically significant. Results Of a total of 1237 (79.8%) physicians (43.7% males; mean age 47.5 ± 11.6 years, 46.3% general practitioners) 24.8% considered generic drugs to be less safe, especially those with specialized qualification (p < 0.01). However, only 4.4% of the physicians noticed any drug-related problems, including adverse drug reactions associated with generic substitution. The majority of physicians felt neutrally about performing generic substitution in pharmacies, nor they expressed any opinion on characteristics of generics, even though a better understanding of the legislation and higher need of accordance of substituted drugs were associated with more positive attitudes towards generic substitution (p < 0.05). Physicians showed low knowledge score of legislative rules (mean 3.9 ± 1.6 from maximum 9), nevertheless they overestimated the law, as they considered some rules valid, even if the law does not require them. Cronbach alpha of all legislative rules that regulate generic substitution increased from 0.318 to 0.553 if two optional rules (physician consent and strength equivalence) would be taken into account. Conclusions There is no sufficient awareness of generic drugs and generic substitution related issues among Czech physicians, although a deeper knowledge of legislation improves their perception about providing generic substitution.